2001
DOI: 10.3386/w8630
|View full text |Cite
|
Sign up to set email alerts
|

DotCom Mania: The Rise and Fall of Internet Stock Prices

Abstract: This paper provides one potential explanation for the rise, persistence and eventual fall of internet stock prices. Specifically, we appeal to a model of heterogenous agents with varying degrees of beliefs about asset payoffs who are subject to short sales constraints. In this framework, it is possible that "optimistic" investors overwhelm "pessimistic" ones, leading to prices not reflecting fundamental values about cash flows summarized by aggregate beliefs. Empirical support for this explanation is provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
347
3
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(374 citation statements)
references
References 23 publications
(36 reference statements)
19
347
3
5
Order By: Relevance
“…Even on average, however, short-selling constraints could impede a symmetric negative position (see, e.g., Hong and Stein, 2003, Ofek and Richardson, 2003, and Lamont and Jones, 2002. Hence, portfolios of agents with private investors may appear to be under-diversified in the cross-section.…”
mentioning
confidence: 99%
“…Even on average, however, short-selling constraints could impede a symmetric negative position (see, e.g., Hong and Stein, 2003, Ofek and Richardson, 2003, and Lamont and Jones, 2002. Hence, portfolios of agents with private investors may appear to be under-diversified in the cross-section.…”
mentioning
confidence: 99%
“…Ofek and Richardson (2001) contended that part of the reason for these declines has been an increase in the number of shareholder selling driven by the expiration of lock-up agreements. Garicano and Kaplan (2002) found that after the bursting of the tech bubble in 2000, in valuing B2B and B2C e-commerce businesses, the market reduced its expectations regarding future growth, the extent of transaction cost reductions, the speed of the adoption network effect, and the level of competition.…”
Section: Discussionmentioning
confidence: 99%
“…There were higher shorting interest for Internet stocks, higher borrowing costs for shorting Internet stocks, and greater violation of put call parity for Internet stocks in the options market (e.g., Ofek and Richardson (2003)). This figure is taken from Figure 5 of Lamont and Thaler (2003).…”
Section: The Internet Bubblementioning
confidence: 99%
“…The firm insiders such as entrepreneurs and venture capitalists were initially restricted from selling their shares during the so-called lockup periods. According to Ofek and Richardson (2003), the lockup restrictions of a large number of Internet firms expired in early 2000. The subsequent selling by firm insiders put downward pressure on the share prices and caused the asset float (i.e., the number of tradable shares) of these firms to increase substantially, which in turn made short-selling of their stocks easier.…”
Section: The Internet Bubblementioning
confidence: 99%
See 1 more Smart Citation